SOCIAL VALUES IN THE NOVEL SUNSET WITH ROSIE BY TERE LIYE - Harahap, Andi Syahputra; Muliatik, Sri (Program Studi Pendidikan Bahasa Indonesia FKIP-UNIVA Medan, 2024)
The novel Sunset with Rosie by Tere Liye captures the setting of the impact of the bomb that occurred in Bali regarding the lives of Tegar and Rosie's family. There are many social values ​​that can be found in the novel. Tegar's sincerity in leaving his new life in Jakarta to look after Rosie and her children, the relationship between Tegar and Rosie's children, the willingness of Rosie's children not to hate the Bali Bombing perpetrators, and so on. Based on the quote above, researchers are interested in researching the social values ​​contained in the novel Sunset Bersama Rosie by Tere Liye, because nowadays social criticism has become a problem that requires a lot of action. Especially in the world of learning. The title of the scientific work is